The effectiveness of multimedia in the learning and simplification of reproduction topic in science - Intan Saripuddin; Nur Farha Shaafi (Universiti Teknologi MARA, 2025)
The purpose of this study is to investigate the effectiveness of multimedia in the learning and simplification (LnS) of reproduction of form 1 science and their influence towards students’ science achievement. A total of 42 form 1 students from one of the schools in Kota Kinabalu were selected as respondents in this study. This study uses a quasi-experimental approach. This research using a pre-test and post-test design with only one group of respondents. This design involves administered a pre-test, then exposing them to an intervention of LnS using multimedia, and then measuring them again on the post-test. The pre-test and post-test scores will be collected and analyzed using the SPSS version 29 application. Data will be analyzed using descriptive and paired sample t-test methods. The results showed a significance Mean difference of 13.59 between pretest and post-test. It was concluded that multimedia-based learning used in LnS enhanced better students’ academic achievements in the topic of reproduction.